2022
DOI: 10.3390/molecules27134036
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of the Iron Chelator, DIBI, in Experimental Acute Lung Injury

Abstract: Iron plays a critical role in the immune response to inflammation and infection due to its role in the catalysis of reactive oxygen species (ROS) through the Haber-Weiss and Fenton reactions. However, ROS overproduction can be harmful and damage healthy cells. Therefore, iron chelation represents an innovative pharmacological approach to limit excess ROS formation and the related pro-inflammatory mediator cascades. The present study was designed to investigate the impact of the iron chelator, DIBI, in an exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…We observed a significant increase in lung histopathology injury scores following intranasal administration of LPS from P. aeruginosa at 4 and 6 h post-induction. Similar timepoints have been demonstrated in previous studies employing LPS from common respiratory pathogens, P. aeruginosa and E. coli [ 30 , 31 ]. Notably, intranasal saline administration was associated with a minor increase in lung histopathology vs. naïve ( Figure S1 ).…”
Section: Discussionsupporting
confidence: 84%
“…We observed a significant increase in lung histopathology injury scores following intranasal administration of LPS from P. aeruginosa at 4 and 6 h post-induction. Similar timepoints have been demonstrated in previous studies employing LPS from common respiratory pathogens, P. aeruginosa and E. coli [ 30 , 31 ]. Notably, intranasal saline administration was associated with a minor increase in lung histopathology vs. naïve ( Figure S1 ).…”
Section: Discussionsupporting
confidence: 84%
“…Life-threatening systemic inflammation (cytokine storm) can be triggered by various pathological conditions [39,40]. We used LPS to induce ALI in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 mice were challenged with 5 mg/kg lipopolysaccharide (LPS) via intranasal instillation to induce experimental ALI [40]. Briefly, the mice were anesthetized using 5% isoflurane in the presence of oxygen.…”
Section: Experimental Model Of Acute Lung Injury (Ali)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compared to conventional iron chelators, DIBI has a low toxicity profile and has been extensively studied for a wide variety of iron chelation applications [ 90 , 91 , 92 , 93 , 94 ]. Our group has recently reported that through binding to extracellular iron and reducing overall iron bioavailability, DIBI administration significantly attenuated LPS-induced tissue damage, inhibited inflammatory mediator release, and improved microcirculation in ALI [ 95 ]. Experimental studies utilizing iron chelators in ALI are shown in Table 1 .…”
Section: Potential Therapeuticsmentioning
confidence: 99%